PRESPEKTIF MAX WEBER : Analisis Motivasi Orang Tua Memilih Sekolah SDN Gampeng II Prespektif Max Weber - Eka Candra Ali Fauzi (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
ABSTRACTThis study discusses the discussion about education in elementary schools, the community in Gampeng village, Ngluyu sub-district seems to prefer the educational institution of SDN Gampeng II as basic education compared to other basic education institutions. Various reasons appear in line with the actions they take. This study discusses the analysis of the motivation of parents to choose education in elementary schools at SDN Gampeng II. The purpose of this study was to understand the motivations of parents in choosing education for their children, namely at SDN Gampeng II, to find out the reasons for choosing education at SDN and also to know the motives for choosing education at public elementary schools. The theory used is the theory of social action from Max Weber, while the research method used is a qualitative method with a Grounded Theory approach. The results showed that most parents chose to study at SDN Gampeng II because their families were all alumni of SDN Gampeng II as well as their surrounding environment also tended to send their children to SDN Gampeng II. ABSTRAKPenelitian ini membahas mengenai pembahasan seputar pendidikan di sekolah dasar, masyarakat di desa Gampeng kecamatan Ngluyu terlihat lebih memilih lembaga pendidikan SDN Gampeng II sebagai pendidikan dasar dibandingkan dengan lembaga pendidikan dasar yang lainnya. Berbagai alasan muncul sejalan dengan tindakan yang mereka lakukan. Penelitian ini membahas mengenai analisis motivasi orang tua memilih pendidikan di sekolah dasar di SDN Gampeng II. Tujuan dari penelitian ini adalah untuk memahami motivasi orang tua dalam memilih Pendidikan untuk anaknya yaitu di SDN Gampeng II, mengetahui alasan memilih pendidikan di SDN dan juga mengeahui motif memilih pendidikan di sekolah dasar negeri. Teori yang digunakan adalah teori tindakan sosial dari Max Weber, sedangkan metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan Grounded Theory. Hasil penelitian menunjukkan bahwa sebagian besar orang tua memilih pendidikan di SDN Gampeng II ialah kerena keluarga mereka semua alumni SDN Gampeng II begitupun lingkungan sekitar mereka juga cenderung menyekolahkan anaknya di SDN Gampeng II.